2019
DOI: 10.1016/j.molliq.2019.111118
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-modified magnetic graphene oxide surface: Feasible adsorbent for removal of dyes

Abstract: Magnetic nanoparticles were integrated with graphene oxide sheets modified by metformin to introduce polyamine functionality in structure. Modified magnetic graphene oxide by metformin (MMGO) adsorption ability was studied for removal of methyl violet (MV) and acid red 88 (AR88) at different pH, initial concentration, and contact time. The successful preparation of magnetic nanoparticles supported with modified graphene oxide sheets is evident from FTIR spectra, TGA, zetapotential and magnetic measurements. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…At present, there are over 9000 dyes types included in the colour index for various chemical applications in the colouring industries (Q. . Acid red 88 (AR88) is a synthetic anionic red azo dye commonly employed by textile and other industries associated with colouring their products (Abdi et al, 2019). This huge consumption of these synthetic dyes and water by industries as their main raw materials results into a high pollutant load for produced effluents.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are over 9000 dyes types included in the colour index for various chemical applications in the colouring industries (Q. . Acid red 88 (AR88) is a synthetic anionic red azo dye commonly employed by textile and other industries associated with colouring their products (Abdi et al, 2019). This huge consumption of these synthetic dyes and water by industries as their main raw materials results into a high pollutant load for produced effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have shown that graphene-based membranes have great potential in filtration, separation and water desalination. Addition of GO (~ 1% rather than mass of polymer) can significantly improve the hydrophilicity, permeability and antifouling performance of the membranes [75][76][77].…”
Section: Fluoropolymeric Membranes: Pvdf and Ptfementioning
confidence: 99%
“…In recent years, magneticloaded adsorbent particles based on Fe 3 O 4 nanoparticles have obtained special attention in wastewater treatment [18][19][20][21][22][23][24][25], due to their easy recovery from the solutions by a simple, low-cost external magnetic field. Various magnetic sorbents [26,27], which are designed by making surface modifications to some special functional groups to target dyes, have dyes, have been developed to treat the corresponding dyes' wastewater. However, the majority of the magnetic adsorbents developed show relatively low adsorption capacities for objective dyes [28][29][30], and the stability of Fe3O4 nanoparticles against acidic erosion needs to be improved to increase their service time and applications in acidic conditions [31].…”
Section: Introductionmentioning
confidence: 99%